Повышение конкурентоспособности российских промышленных холдингов путем внедрения усовершенствованной модели реализации инвестиционных программ (Путеводитель предпринимателя)
The paper considers the problem of improving the competitiveness of Russian industrial holdings. Proposed to develop an improved model of the industrial holding company in order to improve its sustainability and competitiveness.